2017
DOI: 10.1017/s0033291717001076
|View full text |Cite
|
Sign up to set email alerts
|

Altered activation of the ventral striatum under performance-related observation in social anxiety disorder

Abstract: The present findings emphasize the importance of social-context processing in SAD by showing that scrutiny prevents appropriate reward-processing-related signatures in response to positive performances in SAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 57 publications
2
29
0
Order By: Relevance
“…We found comparable activation in VMPFC to RPE in both groups and both conditions. This suggests that VMPFC did not distinguish between the observation and control conditions (see also Simon et al, 2014, Becker, Simon et al, 2017). Furthermore, VMPFC activation did not distinguish between SAD and HC.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We found comparable activation in VMPFC to RPE in both groups and both conditions. This suggests that VMPFC did not distinguish between the observation and control conditions (see also Simon et al, 2014, Becker, Simon et al, 2017). Furthermore, VMPFC activation did not distinguish between SAD and HC.…”
Section: Discussionmentioning
confidence: 99%
“…However, Heitmann et al (2014) found elevated anticipatory DMPFC activation in subclinical social anxiety to positive and negative feedback provided by human raters. Becker, Simon et al, (2017) reported a region in MPFC to show an interaction of feedback valence, observation, and SAD diagnosis. However, no study thus far has shed light on the computational mechanisms at the heart of these phenomena.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations